2006
DOI: 10.1093/jb/mvj015
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Chromatin Remodeling Complex SWI/SNF Is Essential for Enhanced Expression of the Albumin Gene during Liver Development

Abstract: The chromatin remodeling complex SWI/SNF is known to regulate the transcription of several genes by controlling chromatin structure in an ATP-dependent manner. SWI/SNF contains the Swi2p/Snf2p like ATPases BRG1 or BRM exclusively. We found that the expression of BRM gradually increases and that of BRG1 decreases as liver cells differentiate. Chromatin immunoprecipitation assays revealed that the ATPase subunits of SWI/SNF and tumor suppressor retinoblastoma (RB) family proteins bind to the promoter region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…We and other groups have shown that C/EBP␣ interacts with BRG1, an ATPase subunit of SWI/SNF chromatin remodeling complex (14) and C/EBP␣-mediated transactivation of the albumin gene is enhanced by the SWI/ SNF complex in hepatocytes (25). Because the binding site for BRG1 in C/EBP␣ overlaps with the SUMO-1 conjugation site (Fig.…”
Section: Modification Of C/ebp␣ By Sumo-1 Decreases the Cooperation Bmentioning
confidence: 91%
See 3 more Smart Citations
“…We and other groups have shown that C/EBP␣ interacts with BRG1, an ATPase subunit of SWI/SNF chromatin remodeling complex (14) and C/EBP␣-mediated transactivation of the albumin gene is enhanced by the SWI/ SNF complex in hepatocytes (25). Because the binding site for BRG1 in C/EBP␣ overlaps with the SUMO-1 conjugation site (Fig.…”
Section: Modification Of C/ebp␣ By Sumo-1 Decreases the Cooperation Bmentioning
confidence: 91%
“…The mammalian expression vector pSPORT6/mPIASy (MGC 35863) was purchased from Invitrogen. A pREP4-based luciferase reporter plasmid in which the luciferase gene is under the control of the albumin promoter, pcDNA4/C/EBP␣, pcDNA4/BRG1, pcDNA4/mutBRG1 (ATPase mutant) and pcDNA4/BRM, was described previously (25). Mutant C/EBP␣ expression vectors were generated by site-directed mutagenesis by replacing Lys-159 with Ala or Arg.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of SWI/SNF by all indications is far reaching. In mammals it is involved in many developmental programs such as muscle [19][20][21][22], heart [23], blood [24], skeletal [25], neuron [26][27][28][29], adipocyte [30], liver [31] and immune system/Tcell development [32,33]. Yeast SWI/SNF has been shown to be involved in an early step in homologous recombination (HR) while RSC promotes HR at the stage of strand invasion [34,35].…”
Section: Nucleosome Remodeling Complexes Swi/snf Familymentioning
confidence: 99%